An Optical/Photoacoustic Dual-Modality Probe: Ratiometric in/ex Vivo Imaging for Stimulated H2S Upregulation in Mice - Chen, Zhongyan; Mu, Xueling; Han, Zhong; Yang, Shiping; Zhang, Changli; Guo, Zijian; Bai, Yang; He, Weijiang (Journal of the American Chemical Society, 2019)
Tracking signaling H2S in live mice demands responsive imaging with fine tissue imaging depth and low interferences from tissue scattering/autofluorescence and probe concentration. With complementary advantages of fluorescence and photoacoustic (PA) imaging, optical/PA dual-modality imaging was suggested for in/ex vivo H2S imaging. Therefore, a meso-benzoyloxyltricarboheptamethine cyanine, HS-CyBz, was prepared as the first ratiometric optical/PA dual-modality probe for H2S, profiting from a keto–enol transition sensing mechanism. Tail intravenous injection of this probe leads to probe accumulation in the liver of mice, and the endogenous H2S upregulation triggered by S-adenosyl-l-methionine has been verified by ratiometric optical/PA imaging, suggesting the promising potential of this ratiometric dual-modality imaging.